PTU-164 Cost Effectiveness of an ER Dominant Approach in the Management of High Grade Intraepithelial Neoplasia and Mucosal Cancer in Barrett'S Oesophagus. (4th June 2013) - Basford, P J; Longcroft-Wheaton, G; Mead, R; Bhandari, P
Abstract : Introduction: Endoscopic resection (ER) is an established effective treatment for high grade intraepithelial neoplasia (HGIN) and intramucosal cancer (IMC) arising in Barrett's oesophagus. ER can lead to recurrence so it is suggested that all patients should undergo radiofrequency ablation (RFA) after ER as a complimentary treatment strategy. However no comparative study to support this concept has been performed. We aimed to compare the cost-effectiveness of an EMR-dominant approach vs an EMR-RFA approach for the treatment of HGIN and IMC in Barrett's oesophagus. Methods: All ER procedures between 2005 and 2012 were recorded in a prospective database which was analysed. Demographic data, histology, procedure success, long-term outcome and complications were assessed. Costs were calculated using NHS HRG codes plus equipment costs for ER and RFA. Results: 92 patients were treated for dysplastic Barrett's oesophagus or early Barrett's cancer by ER. The mean age at first procedure was 69 years and 87% of the patients were male. 21 of 92 patients had advanced histological features on the initial ER specimen and were referred for surgical or oncological treatment. Of the remaining 71 cases, 63 have follow-up data with a mean duration of 4.3 years. 59 of 63 cases (94%) had successful eradication of HGIN/IMC by ER. The remaining 4 patients were referred for surgery for advanced disease (3) or extensive bulky disease not amenable to ER (1). ER was successful in a mean of 1.46 procedures per patient (range 1–3). Complication rate was 5.2% (4 bleeds, 1 microperforation, 2 strictures). Additional RFA was used in 11 cases. 12 (20%) of patients developed recurrence of HGIN/IMC during follow-up requiring further endoscopic therapy. 2 (3.4%) patients developed more advanced Barrett's neoplasia during follow-up. The calculated cost per patient of an ER-dominant approach is £4125 compared to £8868 per patient for an RFA dominant approach. Conclusion: ER acted as an accurate and safe staging procedure in up to 23% of cases found to have advanced histology. ER is an effective and safe treatment for HGIN/IMC within Barrett's oesophagus without the need for routine RFA and can be performed successfully in a UK centre. However the recurrence of HGIN/IMC is not uncommon and therefore close follow-up is required to identify and treat it at an early stage. An ER-dominant approach may offer significant cost-savings compared to an RFA-dominant approach without compromising overall outcomes. Disclosure of Interest: None Declared